Medical versus non medical etiology in out-of-hospital cardiac arrest—Changes in outcome in relation to the revised Utstein template. (January 2017) - Claesson, A.; Djarv, T.; Nordberg, P.; Ringh, M.; Hollenberg, J.; Axelsson, C.; Ravn-Fischer, A.; Stromsoe, A.
Abstract: Introduction: The Utstein-style recommendations for reporting etiology and outcome in out-of-hospital cardiac arrest (OHCA) from 2004 have recently been revised. Among other etiologies a medical category is now introduced, replacing the cardiac category from Utstein template 2004. Aim: The aim of this study is to describe characteristics and temporal trends from reporting OHCA etiology according to the revised Utstein template 2014 in regards to patient characteristics and 30-day survival rates. Methods: This registry study is based on consecutive OHCA cases reported from the Emergency medical services (EMS) to the Swedish Registry of Cardiopulmonary Resuscitation (SRCR) 1992–2014. Characteristics, including a presumed cardiac etiology in Utstein template 2004, were transcribed to a medical etiology in Utstein template 2014. Results: Of a total of n = 70, 846 cases, 92% were categorized as having a medical etiology and 8% as having a non-medical cause. Using the new classifications, the 30-day survival rate has significantly increased over a 20-year period from 4.7% to 11.0% in the medical group and from 3% to 9.9% in the non-medical group (p ≤ 0.001). Trauma was the most common cause in OHCA of a non-medical etiology (26%) with a 30-day survival rate of 3.4% whilst drowning and drug overdose had the highest survival rates (14% and 10% respectively). Conclusion: Based on Utstein 2014 categories of etiology, overall survival after OHCA with a medical etiology has more than doubled in a 20-year period and tripled for non-medical cases. Patients with a medical etiology found in a shockable rhythm have the highest chance of survival. There is great variability in characteristics among non-medical cases.